Revealing the Microscopic Real-Space Excursion of a Laser-Driven Electron - Heiko G. Kurz; Martin Kretschmar; Thomas Binhammer; Tamas Nagy; Detlev Ristau; Manfred Lein; Uwe Morgner; Milutin Kovačev (Physical Review X, 2016)
High-order harmonic spectroscopy allows one to extract information on fundamental quantum processes, such as the exit time in the tunneling of an electron through a barrier with attosecond time resolution and molecular structure with angstrom spatial resolution. Here, we study the spatial motion of the electron during high-order harmonic generation in an in situ pump-probe measurement using high-density liquid water droplets as a target. We show that molecules adjacent to the emitting electron-ion pair can disrupt the electron’s trajectory when positioned within the range of the maximum electronic excursion distance. This allows us to use the parent ion and the neighboring molecules as boundaries for the electronic motion to measure the maximum electronic excursion distance during the high-order harmonic generation process. Our analysis of the process is relevant for optimizing high-harmonic yields in dense media.